The sentinel lymph node biopsy as part of treatment in patients with Paget disease of the breast: a report of two cases - Nejc, Dariusz; Piekarski, Janusz; Pluta, Piotr; Wroński, Konrad; Sęk, Piotr; Jeziorski, Arkadiusz (Contemporary Oncology/Współczesna Onkologia, 2004)
Treatment of patients with Paget disease of the breast is controversial. We present two patients treated in our center. In one case modified radical mastectomy was performed, whereas in the other, breast conserving surgery was performed. In both cases, sentinel node biopsy was performed. Case one. A 78-year-old woman underwent modified radical mastectomy. In order to maximize the sensitivity of pathologic examination, sentinel node biopsy was performed. The day before the surgery preoperative lymphoscintigraphy was performed using 99m Tc on an albumin carrier (radioactivity: 37 MBq; volume: 0.5 ml). The radioactive tracer was injected intradermally at the border of areola. Four injections were performed. Surgery was started with the injection of blue dye using the same injecting technique. Three sentinel nodes were identified also with the use of a hand-held gamma radiation detector. In the removed breast, pathologic examination revealed the presence of multiple small foci of invasive ductal cancer. No metastases were found in sentinel or the other nodes. As the patient’s tumor was estrogen receptor positive, hormonotherapy with tamoxifen was started. Case two. In a 52-year-old woman nipple-areola complex together with the underlying tumor were excised. The patient underwent also sentinel node biopsy; the same technique was used as in the first of described cases. Pathologic examination revealed the presence of invasive ductal cancer (G3), estrogen receptor (-), progesterone receptor (-), Her 2(3+) together with intraductal component. No metastases were found in sentinel node [CK-MNF(-)]. The patient received postoperative radiotherapy and chemotherapy. Summary: The presented cases show in fact a range of surgical interventions in Paget disease patients, from the most aggressive to the most conservative one.